2000
DOI: 10.1038/sj.leu.2401959
|View full text |Cite
|
Sign up to set email alerts
|

Expression and activity of caspases 1 and 3 in myelodysplastic syndromes

Abstract: Myelodysplastic syndromes (MDS) are characterized by abnormal growth of committed progenitors in clonogenic assay, with reduced number of colonies and decreased colony/cluster ratio. It has been suggested that excessive apoptosis is the cause of marrow failure in MDS. We studied the expression of caspase-1 (interleukin-1␤-converting enzyme, ICE) and caspase-3 (CPP32/apopain) in marrow mononuclear cells, and the growth pattern of committed progenitors in a series of 83 MDS cases. The percentage of apoptotic cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 25 publications
7
26
0
2
Order By: Relevance
“…Recently a beneficial effect of caspase 3 inhibition on clonogenic Leukemia potential was strongly supported by a French study, showing significantly higher caspase 3 activity in RA/RARS vs other MDS subtypes, and that the inhibitor DEVD-cho was significantly enhanced in particular erythroid colony growth in these subtypes. 39 Similar to what we observed, there was no effect of caspase inhibition on normal bone marrow. Thus, there is now multiple evidence that increased caspase activation plays an important role in ineffective erythropoiesis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Recently a beneficial effect of caspase 3 inhibition on clonogenic Leukemia potential was strongly supported by a French study, showing significantly higher caspase 3 activity in RA/RARS vs other MDS subtypes, and that the inhibitor DEVD-cho was significantly enhanced in particular erythroid colony growth in these subtypes. 39 Similar to what we observed, there was no effect of caspase inhibition on normal bone marrow. Thus, there is now multiple evidence that increased caspase activation plays an important role in ineffective erythropoiesis.…”
Section: Discussionsupporting
confidence: 86%
“…In our previous study, we showed that a short caspase inhibition of CD34 + cells before plating could improve erythroid clonogenic growth 27 and the French study adding caspase inhibition during the whole culture period showed even stronger positive effects. 39 We also showed that erythroid cells at the GPA+ level was not affected by caspase inhibition, and that caspase activity was lower in this compartment, suggesting that the important steps in erythroid apoptosis in RARS occur at maturation levels before GPA+ cells. The caspase assay is a cell consuming method and we did not have the opportunity to apply it on purified CD34 + cells from more than one RARS and one control (data not shown).…”
Section: Figurementioning
confidence: 53%
“…These studies could also provide new insights in the mechanisms of caspase activation and abnormal differentiation associated with early phases of myelodysplastic syndromes. 47,48 …”
Section: Discussionmentioning
confidence: 99%
“…Both of these techniques can be used to examine the induction of apoptosis. [46][47][48][49][50] An example of these techniques is presented in Figure 6.…”
Section: Pi3k Is Required For Mek1-mediated Growthmentioning
confidence: 99%